Ensemble Modeling with Data Assimilation Models: A New Strategy for Space Weather Specifications, Forecasts, and Science. Issue 3 (20th March 2014) - Schunk, R. W.; Scherliess, L.; Eccles, V.; Gardner, L. C.; Sojka, J. J.; Zhu, L.; Pi, X.; Mannucci, A. J.; Wilson, B. D.; Komjathy, A.; Wang, C.; Rosen, G.
Key Points There is a need to elucidate processes that lead to space weather disturbances Effort is needed to both mitigate and forecast near‐Earth space weather Ensemble modeling will lead to a shift in how physical processes are studied